Breeding biology and novel reproductive behaviour in the Hainan Partridge (Arborophila ardens) - Xiaodong Rao; Canchao Yang; Wei Liang (Avian Research, 2017)
Abstract Background The Hainan Partridge (Arborophila ardens) is endemic to Hainan Island, China, and is listed as vulnerable (VU) because its population size is steadily decreasing due to illegal hunting and habitat loss. Its breeding biology is poorly known. Methods This study was conducted in three sites in the major tropical primary rainforest in Hainan. Nests of the Hainan Partridge were found by monitoring radio-tracked individuals. Video recorders were set up to monitor reproductive behaviour of Hainan Partridge when nests were found. Results Here for the first time we report the breeding biology of Hainan Partridge by providing information on its nest site, nest, eggs, and reproductive behaviour. We found that Hainan Partridges laid immaculate white eggs in ground nests which were totally covered by dry leaves and small branches forming arches that provided optimal concealment. A novel and regular behaviour was found in Hainan Partridges since they grasped leaves and small branches and then threw them on or around their nests to provide cover during incubation and after hatching of chicks. Conclusions Recruitment behaviour in Hainan Partridges benefit from supplementation of nest arch material to nests, cover the nest entrance and thus maintain or increase nest concealment. However, it may also contribute to concealment of the track which could expose their activities and clues for predators. Our finding implies that the Hainan Partridge has evolved such a novel reproductive behaviour under the strong selection of predation pressure. Due to habitat fragmentation and habitat loss, we suggest setting up arch structures and provide small branches and leaves in degraded or fragmented habitats to improve their suitability for partridge reproduction. This method may contribute to increasing the reproductive success of Hainan Partridge and thus compensate for its continuous population decrease.